ENHANCEMENT OF THE DISSOLUTION RATE OF NATEGLINIDE TABLETS USING LIQUISOLID COMPACT TECHNIQUE - Mamatha, Tirunagari; Sultana, Nazia (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The main objective of this work is to develop new formulation to enhance the solubility of a highly permeable and a poorly soluble oral drug antihyperglycemic agent, nateglinide by liquisolid compacts. Methods: The liquisolid compact technique is based on dissolving the insoluble drug in propylene glycol, polyethylene glycol 400, tween-80 as non-volatile solvents in which drug is having high solubility and admixture of drug loaded solution with microcrystalline cellulose as carrier, aerosil as coating material, crospovidone as disintegrant, and magnesium stearate as lubricant to convert into acceptably flowing and compressible powder. The prepared liquisolid compacts were evaluated for their flowing properties such as bulk density, tapped density, angle of repose, Hausner's ratio, and Carr's index. Further tablets were evaluated for hardness, thickness, weight variation, friability, disintegration test, and in vitro release study. Result: Higher drug release profiles due to increased wetting property and surface area of the drug available for dissolution was obtained in case of liquisolid compacts. Among all formulations, liquisolid system prepared by propylene glycol was considered as best formulation which release drug up to 98% in 60 minutes and in comparison to marketed formulation, optimized formulation showed better dissolution profile. Conclusion: It can be concluded that liquisolid compact technique could be a promising strategy in improving the dissolution of poor water soluble drugs.